Strategi Optimalisasi Human Capital dalam Bank BNI 46 untuk Meningkatkan Inovasi dan Layanan - Zuhrofi, Ahmad (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This article examines the strategy for optimizing human capital at Bank BNI 46 to enhance innovation and service quality in the digital era. Human capital is a vital asset in the banking industry, directly influencing operational efficiency and customer satisfaction. Through a literature review, including Bank BNI’s 2023 financial report, the study highlights key strategies such as digital skill development, fostering a culture of innovation, digital transformation in services, and talent management. Bank BNI 46 has implemented initiatives like the Digital Academy and Innovation Hub to upgrade employee capabilities and drive internal innovation. These strategies have resulted in significant improvements, including a 25% increase in mobile banking users and enhanced productivity. However, challenges such as employee resistance to technological changes remain, requiring comprehensive training and change management programs. The findings emphasize that human capital optimization is crucial for sustaining competitive advantage in the fast-evolving banking sector. The research contributes to understanding how strategic human capital management can foster innovation and improve service delivery, offering insights for other banks aiming to navigate digital transformation.